The Influence of Local Culture and Cultural Tourism Activities on the Quality and Reputation of Tourism Destinations in Bandung - Machzumy, Machzumy; Lusianawati, Hayu; Muhtadi, Muhamad Ammar (West Science Social and Humanities Studies, 2024)
This research investigates the influence of local culture and cultural tourism activities on the quality and reputation of tourism destinations in Bandung. A quantitative approach was employed, utilizing survey data collected from 180 tourists visiting cultural attractions in Bandung. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis was conducted to examine the relationships between cultural variables and destination outcomes. The findings reveal significant positive associations between engagement with local culture, participation in cultural tourism activities, and tourists' perceptions of destination quality and reputation. Cultural tourism activities emerge as key drivers of destination quality, while engagement with local culture positively influences destination reputation. These results underscore the importance of cultural assets in enhancing destination attractiveness and visitor satisfaction and highlight opportunities for destination management and tourism development in Bandung and similar cultural destinations.